TEKNOLOGI PRESTO PADA PRODUK BERBASIS IKAN AIR TAWAR KAYA KALSIUM - Nugraheni, Mutiara; Handayani, Titin Hera Widi; Utama, Agung (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
The purpose of this activity is to (1) provide an alternative freshwaterfish post-harvest processing; (2) producing an acceptable using waste fish headsand bones; (3) provide an alternative to consumers in the form of productsmade from freshwater fish that are high in calcium, ready for consumption andhave long-term expired time; and (4) developing agri-based home Industry.These research subjects were Merapi Bangkit dan Sumber Makmur farmergroups in Teplok and Mudal, Argomulyo Village, Cangkringan, Yogyakarta.The method carried out was discussion on proper fish process, hygiene sanitation, food licensing, packaging, marketing strategies and product manufacturing. Competencies evaluation was conducted at the end of the program by producing some product. The evaluation characteristics items were: flavor, color, aroma, texture, innovation and the price per pack. The results show that the alternative fish processing using fish waste that have a long-term expired date can be implemented